2006
DOI: 10.1097/01.mcp.0000239547.62949.82
|View full text |Cite
|
Sign up to set email alerts
|

Induced sputum in interstitial lung diseases

Abstract: We suggest integrating induced sputum technology to the well-established criteria for the diagnosis of interstitial lung diseases, especially when there are clinical contraindications for performing bronchoscopy or when tissue confirmation is absent for any reason.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
2
11
0
1
Order By: Relevance
“…The main reason for this was that induced sputum could not be obtained in 50% of HP patients who underwent SIC. This limited yield is similar to the performance reported by other authors using this technique in patients with interstitial lung disease …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The main reason for this was that induced sputum could not be obtained in 50% of HP patients who underwent SIC. This limited yield is similar to the performance reported by other authors using this technique in patients with interstitial lung disease …”
Section: Discussionsupporting
confidence: 89%
“…Similar features have been observed in patients with idiopathic pulmonary fibrosis, sarcoidosis and scleroderma . This may be because BAL provides information on the distal airway and alveolar spaces, which are rich in macrophages, whereas induced sputum gives evidence of the state of the upper and middle airway, which presents abundant neutrophils . Furthermore, in FHP patients, the significant increase in IL‐8, IL12‐p70 and IL‐1β as compared with BHP could explain the greater increase in neutrophils observed following exposure to fungi.…”
Section: Discussionsupporting
confidence: 57%
“…For this reason, IS is currently considered as a noninvasive tool useful for the detection of airway inflammation in some respiratory diseases, in particular asthma [22]. It has also been suggested that IS might integrate BAL in the diagnosis of ILD when there are contraindications to perform BAL [23]. …”
Section: Discussionmentioning
confidence: 99%
“…In this procedure, patients are stimulated by inhalation of hypertonic saline solution, and attempts are made to expectorate airway secretions non-invasively. IS has been used for studies of sarcoidosis, asthma, and COPD (chronic obstructive pulmonary disease) [7][8][9][10][11][12][13][14]. Here, we aimed to determine whether IS can be used for the diagnostic work-up as well as for monitoring ILD caused by systemic sclerosis.…”
Section: Introductionmentioning
confidence: 99%